Significance of Chemical Reactions and Entropy on Darcy-Forchheimer Flow of H2O and C2H6O2 Convening Magnetized Nanoparticles - Saleem Nasir; Abdallah S. Berrouk; Asim Aamir; Taza Gul (International Journal of Thermofluids, 2023)
The subject of discussion in this analysis is the time independent flow of electrically conducting nanofluid with entropy generation over a radially flexible disk. Considerations for magnetic fields, nonuniform heat generation, Darcy-Forchheimer porous space, dissipation, Ohmic heating and chemical reactions with activation energy are incorporated into the flow distribution. For a number of engineering and biomedical objectives, a mathematical model is introduced with the goal of accelerating the rate of energy transmission and improving the performance and efficiency of heat energy transportation. Titanium dioxide nanomaterial is consisting of two base fluid, water and ethylene glycol (EG), to synthesize the nanofluid (water/TiO2 and ethylene EG/TiO2). Additionally, the second thermodynamic law has been used to model entropy generation. This model takes into account the irreversibility of heat, fluid friction and joule dissipation processes. The problem has been modeled as a set of partial differential equations. That are streamlined into a system of ODEs by using similarity substitutions. The retrieved differential equations are then assessed utilizing computational approach HAM. For consistency and validity, the results are examined using numerical methodology (shooting method). Also, investigations are conducted into the effects of the radiation, magnetic factors, Brinkman number, volume fraction of nanoparticles on the entropy and Bejan number. Moreover, visually and computationally, the impacts of design variables on the movement, temperature and concentration profile, drag force, heat and mass flux rate are explored. The findings exhibit great comparability when examined to those of the articles that were previously published. The planned analysis demonstrates the significance of this nanofluids in industrial, pharmaceutical, chemical and nuclear plants as well as solar and other technologies.